2019
DOI: 10.1121/1.5134063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of acoustic damping performances of double-layer in-duct perforated plates at low Mach and Helmholtz number

Abstract: In this work, acoustic damping performances of double-layer in-duct perforated plates are studied at low Mach (Ma) and Helmholtz number (He) to evaluate the effects of (1)  Ma, (2) the porosities (i.e., open-area ratio) σ1 and σ2 of the front and back plates, and (3) the axial distance Lc between these two plates. The orifices’ damping is characterized by sound absorption coefficient α denoting the fraction of incident sound energy being absorbed. For this, a quasi-steady acoustic model is developed first and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…For double-layer in-duct perforated plates, acoustic damping performances are studied at low Mach and Helmholtz number to evaluate the effects of Mach, the porosities of the front and back plates, and the axial distance between these two plates in (Guan et al ., 2019b). It is found that sound absorption coefficient is periodically changed over the interested range of Helmholtz number, when Mach = 0.…”
Section: Simulation Of the Sound Absorption Performancementioning
confidence: 99%
“…For double-layer in-duct perforated plates, acoustic damping performances are studied at low Mach and Helmholtz number to evaluate the effects of Mach, the porosities of the front and back plates, and the axial distance between these two plates in (Guan et al ., 2019b). It is found that sound absorption coefficient is periodically changed over the interested range of Helmholtz number, when Mach = 0.…”
Section: Simulation Of the Sound Absorption Performancementioning
confidence: 99%
“…The noise damping performance of a tested sample/material is characterized by using sound absorption coefficient Δ a ( ω ), which is defined as 22 where x 1 and x 2 are the axial locations sensor 1 and sensor 2 in the wave tube, and H(ω) is the transfer function between the two sensors. The sound absorption coefficient indicates the ratio of the incident waves acoustical energy that is absorbed by the tested materials.…”
Section: Experiments Proceduresmentioning
confidence: 99%
“…Maintaining Helmholtz resonators' peak damping performance with operating conditions being changed could be achieved by applying a feedback control strategy. Zhao et al 10 demonstrated how to actively passive control of thermoacoustic instabilities 14 by actively optimizing the damping peaks of multiple Helmholtz resonators. The optimum frequency at which they produce the maximum damping is varied by altering their geometry such as varying the area of the Helmholtz resonator neck.…”
Section: Introductionmentioning
confidence: 99%